Welding symbols on drawings - Gregory, E. N. (CRC Press ; Woodhead, 2005)
This contemporary book provides an up-to-date review on the application of ISO and AWS standards and a comparison between them. Many thousands of engineering drawings are currently in use, which have symbols and methods of representation from superseded standards. The current European and ISO standards and the American standard are substantially similar, but the ANSI/AWS standard includes some additional symbols and also symbols for non-destructive testing. Although symbols in the different standards are similar, the arrows showing locations of welds are different, these important differences.
Keywords: Welding -- Notation.; elektronické knihy; electronic books